Antimicrobial activity of aroylhydrazone-based oxido vanadium(v) complexes: in vitro and in silico studies. (15th January 2016) - Yousef Ebrahimipour, S.; Sheikhshoaie, Iran; Simpson, Jim; Ebrahimnejad, Hadi; Dusek, Michal; Kharazmi, Nima; Eigner, Vaclav
Abstract : A series of oxido vanadium(v ) complexes have been synthesized and evaluated from the point of experimental and theoretical antimicrobial activity. Abstract : A tridentate Schiff base ligand ( E )- N ′-((2-hydroxynaphthalen-1-yl)methylene)benzohydrazide (H2 L ) and its oxido-vanadium(v ) complexes with formulae [VO(L)(MeOH)(OMe)] (1 ), [VO(L)(OEt)] (2 ), and [VO(L)(OPr)] (3 ) have been synthesized and fully characterized by physicochemical and spectroscopic methods including elemental analysis, FT-IR, 1 H NMR and molar conductivity. The solid state structures ofH2 L and complexes1–3 have also been investigated using single crystal X-ray analysis. It was concluded thatH2 L crystallized in keto form in the solid state; however in all complexes, the ligand appears in the enol form. The coordination geometry of complex1 was found to be distorted octahedral while complexes2 and3 adopt square pyramidal geometries. The antimicrobial activity of these compounds was also evaluated against Escherichia coli (ATCC 25922) and Staphylococcus aureus (ATCC 33591 and 29213) bacteria and the results showed that all three complexes have significant antibacterial activities. In order to determine the potential of these complexes as antimicrobial agents, molecular docking of the complexes with GlcN-6-P synthase was also investigated.